A STUDY OF JADIDISM IN THE INDEPENDENCE PERIOD (Journal of Pharmaceutical Negative Results, 2022)
In this article, the observations of literary scholar K.Kahramanov on his assessment of the life and work of modern literary figures who were victims of repression in Uzbek literary studies and criticism of the independence period as a methodological update.